Grit in second language acquisition: a systematic review from 2017 to 2022 - Zhao, Xian; Wang, Danping (Frontiers in Psychology, 2023)
Recent years have witnessed increasing attention to personality strength (grit) due to its merit in goal-seeking language learning processes. Two facets of grit, namely perseverance of effort (PE) and consistency of interest (CI), play a critical role in overcoming learning difficulties and strengthening willpower to pursue learning goals. The current review seeks to explore various issues related to grit, including its factor structure, the relationship between grit and frequently associated factors, as well as the utility of PE and CI in facilitating language learning. This exploration is based on the findings of 32 empirical articles published between 2017 and 2022 from three databases. The results indicate that although research which examines the role of grit has entered a fast growth phase since 2020, there is still a need for expansion and diversification in scopes, participants, research methods, and language contexts. Moreover, previous studies have not adequately addressed the critical issue of grit's conceptualization and factor structure. Finally, this study suggests that future researchers should impartially assess the factor structure and nature of PE and CI to provide more robust evidence to clarify the relationship between grit and diverse emotions and positive institutions, in order to advance understanding of grit in second language learning.